Pedômetro como preditor de mortalidade na DPOC - Nyssen, Samantha Maria (2013)
Objectives: To compare groups with Chronic Obstructive Pulmonary Disease (COPD) who achieved or not the minimum recommendation of 4580 steps per day, recorded by pedometer, with the BODE index variables and their body mass index (BMI), distance covered in 6-minute walk test (6MWT), dyspnea sensation by scale modified Medical Research Council (mMRC) and forced expiratory volume in one second (FEV1). Furthermore, analyzing the correlation between the number of steps with subjective questionnaires of physical activity, age, BODE index and its variables. Methods: Cross-sectional study were evaluated 30 COPD patients divided into group 1 (≥ 4580 steps) and group 2 (<4580 steps), by monitoring with pedometer, short International Physical Activity Questionnaire (IPAQ short) and modified Baecke questionnaire, Index BODE and its variables. The difference analyzes were performed using the Mann-Whitney test or unpaired t test, correlations by Pearson or Spearman test (p <0.05). Results: There were no differences between the groups in relation to the classification score and BODE index and its variables (BMI, FEV1 and mMRC), modified Baecke questionnaire (total score, sports fields and home) and the IPAQ short score (metabolic equivalent domains (MET) in moderate and vigorous activity per week). We observed higher values for group 2 in the modified Baecke questionnaire (leisure domain) and age, and lower values of distance covered in 6MWT, % predicted 6MWT and in the scores IPAQ short domain (MET walk in during the week and total score). It found a weak correlation between the IPAQ short with the number of steps (r = 0.399), with age (r = -0.459), with 6MWT (r = 0.446) and % predicted 6MWT (r = 0.422). Conclusions: The value of 4580 steps suggested in the literature, was not sensitive to reflect differences between the groups when compared with established predictors of mortality. The IPAQ short can be an acceptable and feasible to measure the level of physical activity in patients with COPD.